Classroom Streaming and Academic Achievement Among Students in Secondary Schools in Uganda: Evidence from Apac and Jinja Districts. - Karuhanga, Samuel; Chama, Julius; Bantu, Edward; Tibesasa, Ruth; Turyasingura, Benson (Kabale University, 2024)
Several studies have been conducted to ascertain the impact of ability grouping on academic attainment over the past 20 years, but little effort has been made. The purpose of the study was to investigate the effect of classroom streaming on academic achievement and self- esteem of secondary school students and the relationship between streaming and academic achievement among students in secondary schools in Apac and Jinja districts. The researcher involved four secondary schools from the Apac and Jinja districts. The 240 subjects, both boys and girls, with 30 subjects drawn from each of the selected streams, were drawn from the four schools. The sample chosen was large enough to be representative of the whole student population in the two districts. The analysis of the relationship between streaming and academic achievement revealed that the p-calculated value was found to be 0.0001 with df = 238. Since 0.0001 is far less than 0.05, which is the P-critical value at which the researcher tested the hypothesis, the conclusion is that streaming has an effect on academic achievement. The study confirmed that ability grouping has a strong bearing on the academic achievement of secondary school students.